PENGARUH SALES PROMOTION, BRAND IMAGE DAN INSTORE DISPLAY TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN HYPERMARKET DAN GIANT GRESIK) - Fauziah, Farah (Universitas Muhammadiyah Gresik, 2019)
This study aims to determine how much the Influence of Sales Promotion, Brand Image and Instore Display towards Consumer Purchasing Decisions on Hypermarket Giant Gresik. The population used in this study were Hypermarket Giant Gresik consumers with a total sample of 96 respondents using Non-Probability Sampling technique with a Incidental Sampling approach. Based on the results of the study found the regression equation as follows Y = - 1.907 + 0.488X1 + 0.474X2 + 0.567X3 + e. Based on statistical data analysis, the indicators in this study are valid and reliable. The variable that has the greatest influence is the Instore Display variable with a regression coefficient of 0.567. Hypothesis testing uses t test which shows that the three independent variables, namely Sales Promotion (X1), Brand Image (X2), Instore Display (X3), have proven to significantly influence the dependent variable, namely purchasing decision (Y).